Series of Experiments with Thermal Insulation Coatings Consisted of Vacuum-Hollow Nano-Ceramic Microspheres - David Bozsaky (Acta Technica Jaurinensis, 2018)
Because of the rigorous regulations in the 21st century it has become a serious task for designers to find more effective ways for thermal insulation. One of these options is the application of nanotechnology-based materials. Among nano-scale structured materials the most uncertainties are found about the thermal insulating quality of thermal insulation coatings consisted of vacuum-hollow nano-ceramic microspheres. Complete agreement had not been already found about the mechanism of their insulating effect. In order to explore and describe the thermodynamic process inside nano-ceramic coatings (NCC) 6 series of heat transfer resistance experiments were performed in 2014-2017. Several building structure configurations with 12 different orders of layers were tested with a standard heat flow meter. On basis of these results it could be concluded that in case of nano-structured materials convective heat transfer coefficient might be taken account in different way than in case of traditional macro-structured thermal insulation materials.